Acute nicotine vapor attenuates sensorimotor gating deficits in HIV-1 transgenic rats. - Jha, Neal A.; Ayoub, Samantha M.; Flesher, M. Melissa; Morton, Kathleen; Sikkink, Megan; Guglielmo, Giordano de; Khokhar, Jibran Y.; Minassian, Arpi; Brody, Arthur L.; Young, Jared W. (Psychopharmacology, 2025)
Rationale: Despite improved life expectancy of people with HIV (PWH), HIV-associated neurocognitive impairment (NCI) persists, alongside deficits in sensorimotor gating and neuroinflammation. PWH exhibit high smoking rates, possibly due to neuroprotective, anti-inflammatory, and cognitive-enhancing effects of nicotine, suggesting potential self-medication. Objectives: Here, we tested the effects of acute nicotine vapor exposure on translatable measures of sensorimotor gating and exploratory behavior in the HIV-1 transgenic (HIV-1Tg) rat model of HIV. Methods: Male and female HIV-1Tg (n = 28) and F344 control rats (n = 29) were exposed to acute nicotine or vehicle vapor. Sensorimotor gating was assessed using prepulse inhibition (PPI) of the acoustic startle response, and exploratory behavior was evaluated using the behavioral pattern monitor (BPM). Results: Vehicle-treated HIV-1Tg rats exhibited PPI deficits at low prepulse intensities compared to F344 controls, as seen previously. No PPI deficits were observed in nicotine-treated HIV-1Tg rats, however. Nicotine vapor increased locomotor activity across genotypes. Cotinine analyses confirmed comparable levels of the primary metabolite of nicotine across genotypes. Conclusions: Previous findings of PPI deficits in HIV-1Tg rats were replicated and, importantly, attenuated by acute nicotine vapor administration. Evidence for similar cotinine levels suggest a nicotine-specific effect in HIV-1Tg rats. Therefore, acute nicotine administration may be beneficial for attenuating sensorimotor deficits in PWH. Future studies should determine the long-term effects of nicotine vapor on similar HIV/NCI-relevant behaviors.